STATE OF SEED-GROWING AND VARIETY CONTENT OF WINTER WHEAT IN THE ROSTOV REGION - G. A. Filenko (Зерновое хозяйство России, 2018)
During a long reproduction any variety tends to decrease its economic-biological traits and properties, which it initially possesses. The reasons for this are different diseases, especially infectious, mechanical and biological littering, which results in decreasing of productivity and grain quality of winter wheat. To overcome it we have to carry out a variety upgrade (renewal), e.i. replacement of the low productive seeds with highly productive ones possessing good sowing features.  In the Rostov region winter wheat is one of the basic grain crops. During last 14 years its area varied from 813,1 (in 2000) till 2096,5 thousand ha (in 2014). The maximum productivity was 36,7 c/ha in 2004. The work gives the average data about the amount of sown original, basic and reproductive seeds of winter wheat in the Rostov region during 2012-2014 years. 38.300 tons of original and basic seeds of winter wheat were sown in 2012, 26.500 t in 2013 and 37.700 t in 2014. Nevertheless, we should note the fact that the most part of the area was sown with the seeds of 1-4 reproduction. We have been analyzing the variety content of winter wheat in different parts of the Rostov region. The main breeding institutions-originators which produce winter wheat varieties for the Rostov region in 2014 are ARRIGC (38,4%), DRIA (28,6%) and KRIA (27,8%), the seeds of which were sown on 94,8% of the area. The varieties of SRIA and SSI occupied 4,6% of the area, the rest (0,6%) belonged to the cultivars of the other institutions.